Detection of pmtv using polyclonal antibodies raised against a capsid-specific peptide antigen / detección de pmtv utilizando anticuerpos policlonales contra un péptido antigénico derivado de la cápside viral (2013)
Potato mop-top virus (PMTV; genus Pomovirus;family Virgaviridae) is the causing agent of the spraing disease in potato (Solanum tuberosum). PMTV is transmitted by Spongospora subterranea f. sp. subterranea (Sss). This disease has a widespread distribution in potato growing regions around the world. The possibility of obtaining strain specific antibodies at low cost can greatly increase the sensitivity and use of serological tests in seed certification programs, plant breeding and quarantine regulations to avoid dissemination of this injurious virus. This work presents an alternative procedure for the production of PMTV specific antibodies useful in serological test such as ELISAand lateral flow. In contrast to standard methods requiring theisolation of viral particles or expression of recombinant capsid, this method uses peptides mimicking the N-terminal region of PMTV capsid protein as antigen for the production of specific polyclonal antibodies. The antibodies were tested against bait plants grown in soil infested with viruliferous Sss, as well as potato plants obtained from naturally Sss infested fields in Colombia. PMTV was detected in 9/14 and 24/28 foliage samples of N. benthamiana and S. phureja, respectively. In the case of field plants, the virus wasdetected in eight out of 12 root tissues evaluated. The minimumpeptide concentration detected by ELISA was of the order of 0.1 nM. / Potato mop-top virus (PMTV; género Pomovirus; familia Virgaviridae) es transmitido por Spongospora subterranea f. sp. subterranea (Sss), agente causal de la sarna polvosa de la papa. Esta enfermedad tiene una amplia distribución en las regiones cultivadoras de papa alrededor del mundo. La posibilidad de obtener anticuerpos específicos contra cepas de este virus, puede incrementar la sensibilidad y la utilización de pruebas serológicas en programas de certificación de semilla, mejoramiento genético y regulaciones cuarentenarias que eviten su diseminación azonas libres de la enfermedad. En esta investigación, se presenta un procedimiento alternativo para la producción de anticuerpos específicos para PMTV de utilidad en pruebas serológicas comoELISA y flujo lateral. A diferencia de los métodos estándar querequieren del aislamiento de partículas virales o de la expresión de cápside recombinante, este sistema utiliza un péptido que simula la región N-terminal de la proteína de la cápside de PMTV, como antígeno para la producción de anticuerpos policlonales. Dichos anticuerpos fueron evaluados en plantas señuelo sembradas en suelos infestados con quistosoros de Sss, así como en plantas de papa obtenidas de suelos de Colombia con infección natural de Sss. La utilización de estos anticuerpos permitió la detección delPMTV en 9/14 y 24/28 muestras foliares de N. benthamianay S. phureja, respectivamente. Para el caso de plantas de papa obtenidas del campo, las pruebas detectaron el virus en ocho de 12 raíces evaluadas. La concentración